EFFECT OF DIFFERENT ADJUVANTS USED IN FOOT AND MOUTH DISEASE VIRUS VACCINE ON ANTIBODY RESPONSE OF BUFFALO CALVES - K. Muhammad; M. A. Tariq; I. Altaf; M. Rabbani; R. M. Khawaja; Q. Akram; M. A. Ali; K. Hanif (Journal of Animal and Plant Sciences, 2013)
Foot and Mouth Disease (FMD) is a viral problem of cloven footed animals such as buffaloes, cattle, sheep, goats, camels, wild animals, etc. The disease outbreaks have been recorded even in the vaccinated dairy animals. The disease is causing heavy economic losses to the dairy industry. Efforts were made to monitor effect of different adjuvants used in FMD vaccine on antibody response of buffalo calves. In each type of vaccines, local FMD virus “serotype “O” having 106 units/ml of mean tissue culture infective dose (TCID50) was used. The binary ethylene immine inactivated FMD virus suspension was mixed with either of montanide-ISA-70 (OB), lanolin and aluminum hydroxide gel (AHG) for production of homogenized vaccines. Each of the adjuvant containing vaccines (3 ml dose) induced detectable level of anti-FMD virus neutralizing antibody titer (Anti-FMDV-VN) in buffalo calves. Subcutaneous injection of the OB vaccine induced sterile abscess or granuloma formation at the inoculation site while deep intramuscular injection showed un-detectable reactions. In contrast to AHG based vaccines, the OB vaccine induced antibody response latter and showed higher boosting response. The antibody titer (>10 units of anti-FMDV-VN) in serum of the animals vaccinated with OB vaccine persisted for more than 240 days post priming. It is concluded that montanide ISA-70 based FMD virus vaccine induces protective antibody titer that persists for more than eight months and vaccination of dairy animals with the OB FMD vaccine twice a year could be an effective way of immunoprophylaxis.
Keywords: Foot and Mouth Disease vaccine; Buffalo; Adjuvant; Antibody response